Biopolymers and Biomacromolecules Solvent Dynamics. Issue 1 (January 2014) - Rossi, Claudio; Bonechi, Claudia; Foletti, Alberto; Magnani, Agnese; Martini, Silvia; Bulavin, Leonid; Guenet, Jean‐Michel
Summary Biomacromolecules in solution modify the structure and the dynamics of the bulk water at the solute‐solvent interface. The ordering effects of biomolecules, in particular proteins, are extended for several angstroms. The role of the hydration shells around a protein has yet to be completely understood. Hydrated proteins maintain more dynamic flexibility with respect to the dried system, which is an important property in protein‐protein and/or protein‐ligand recognition processes. In this paper we propose a method for analyzing the dynamical properties of the water molecules present in the hydration shells of proteins. The approach is based on analysis of the effects of protein‐solvent interactions on water protons NMR relaxation parameters. The water proton spin‐lattice relaxation rate in protein solution is analyzed considering all possible dipolar contributions from coupled protons environments. The analysis of both selective and non‐selective water spin‐lattice relaxation rates allowed the calculation of the average effective correlation time for the water molecules at the protein interface and the evaluation of the long range ordering effect of the protein surface.